"Obstacles to Implementing Total Quality in Technical Education Institutions in the City of Benghazi" (Journal of human and social sciences, 2026)
The advancement of nations depends on the success of their educational systems and the development of human capacities. Education is pivotal for knowledge, technology, innovation, and excellence. To achieve these goals, quality in education has become a central focus, structured through mechanisms and standards that enhance curricula, teaching staff competencies, infrastructure, and assessment processes. These standards ensure high-quality learning outcomes and align educational institutions with labor market needs.In Libya, the National Center for Quality Assurance and Accreditation of Educational and Training Institutions (established in 2010) promotes quality culture across public and private institutions. The center conducts institutional and programmatic accreditation based on comprehensive domains including strategic planning, academic programs, faculty, student services, research, community engagement, continuous improvement, and transparency. Evaluation follows a point-based system with thresholds for preliminary and final accreditation, ensuring compliance with national and international standards.Despite these efforts, many Libyan institutions face challenges such as limited resources, low awareness of quality standards, and insufficient implementation, resulting in a small number of accredited institutions. Strengthening quality assurance and accreditation mechanisms is crucial for improving the performance and global competitiveness of Libyan higher education.
Keywords: Educational Quality Assurance; Institutional and Programmatic Accreditation; Higher Education Development; National Center for Quality Assurance; Human Capabilities and Labor Market